Investigating the effect of exchange rate changes on the People's Republic of China's processed exports - Willem Thorbecke (Asian Development Bank Institute (ADBI), 2010)
Many argue that the yuan needs to appreciate to rebalance the People's Republic of China's trade. However, empirical evidence on the effects of a CNY appreciation on the People's Republic of China's exports has been mixed for the largest category of exports, processed exports. Since much of the value-added of these goods comes from parts and components produced in Japan, the Republic of Korea, and other East Asian supply chain countries, it is important to control for exchange rate changes in these countries. Employing dynamic ordinary least squares, or DOLS, techniques and quarterly data, this paper finds that exchange rate appreciations across supply chain countries would cause a much larger drop in processed exports than a unilateral appreciation of the yuan.
Keywords: F32; F41; 330; Wechselkurs; Volatilität; Außenhandelseffekt; Veredelungsverkehr; Schätzung; China